Potential of digitalization within physiotherapy: a comparative survey - Katharina Estel; Julian Scherer; Heiko Dahl; Eva Wolber; Noah D. Forsat; David A. Back (BMC, 2022)
Abstract Background Due to the global digitalization, implementation of digital elements into daily work can support physiotherapists' work but may also pose some challenges. Only little is known about physiotherapists' attitude towards digitalization. This study primarily aimed to analyze physiotherapists' attitude towards digitalization and to what extend digital tools have been implemented into their daily work. In second analysis, participants' characteristics such as age, working place, gender and mode of survey participation were assessed. Methods A 12-main-item survey amongst voluntary course participants of one physiotherapeutic training center was conducted via paper-based as well as online questionnaires between July 2018 and June 2019 including questions on participants' general as well as particular attitude towards digitalization, the use of (mobile) applications and possible advantages and disadvantages of the ongoing digital transformation. Sub-analysis was performed for age (≤40 years versus > 40 years), gender, mode of participation (paper vs. online) and working place (practice vs. hospital). Results Overall, 488 physiotherapists participated in the survey. In comparison of the age groups, younger participants had more concerns about data security (p = 0.042) and insufficient financial remuneration (p < 0.001). Younger participants stated higher satisfaction with data literacy than their counterparts (p = 0.0001). Physiotherapists working in the outpatient sector, rather than in hospitals, expected digitalization to increase more in relevance (p < 0.001). The online respondents (OG) indicated that they had more knowledge about key aspects of the current legal situation regarding digitalization than participants completing the paper-based survey (p = 0.002). 50.4% of the considered digitalization as useful for their job. Conclusions The majority of participants saw high potential for digitalization in the physiotherapy sector. Younger physiotherapists seem to be more concerned about data security and insufficient financial remuneration. Physiotherapists in the outpatient sector seem to see more potential in digital transformations. General concerns like missing reimbursement, lack of data security or knowledge on legal frameworks should be addressed in the future. Further studies should focus on identifying specific digital tools which can support physiotherapists.